Pendidikan Islam di Era Digital - Gultom, Yusrina; Candra, Dewi; Dasopang, Muhammad Darwis; Sihombing, Irwandi; Ali, Muttaqin Kholis (Indo-MathEdu Intellectuals Journal, 2025)
Islamic education in the digital era faces challenges as well as significant opportunities in presenting Islamic values to the younger generation. This literature study method aims to analyze the influence of digital technology developments on Islamic education, especially in the aspects of curriculum, learning methods, and media used. Digital literacy is the main skill that educators must have to effectively integrate technology into the learning process. Platforms such as Islamic-based learning apps, e-learning, and social media have become potential tools in conveying religious teachings in an engaging and interactive manner. Threats in the form of access to negative content, lack of information filters, and potential deviations in moral values are also a concern. This research finds the importance of the role of teachers, parents, and educational institutions in ensuring that technology is used wisely to support the strengthening of Islamic character and moral character. Proper use of digital resources, Islamic education can remain relevant and adaptive to the needs of the times without overriding the essence of religious values. This article emphasizes the need for synergy between technology and spiritual approaches in shaping a generation of intelligent, faithful, and noble Muslims.